Control of black dot: Integrating agronomy and storage - Peters, Jeff C; Hilton, Alex J; Lees, Alison K; Brierley, Jennie L; Gladders, P; Bradshaw, Nick; Wale, Stuart J (MTT, 2007)
The trend towards washed and packed potatoes for the fresh market has led to an increase in demand for tubers with a good visual appearance. As a consequence of this, blemish diseases, and black dot in particular, are increasingly becoming concerns for the industry (Lees & Hilton, 2003). In GB alone, it is estimated that the blemish diseases, silver scurf and black dot, reduce the value of the total annual crop by around 4.5m. Black dot, caused by the fungus Colletotrichum coccodes has become particularly important because the pathogen is widespread in GB soils and there are limited control options. Field and storage experiments were set up to investigate the interaction between soil inoculum levels for C. coccodes (between 40 and 500 pg DNA/g soil), crop duration and storage regime on black dot development throughout storage. There was an interaction between soil inoculum level and crop duration (measured as days from 50% emergence to harvest) on black dot tuber severity at harvest. Black dot severity increased with lengthening crop duration, and the severity increased more rapidly at higher soil inoculum (P=0.005). Disease progress curves for black dot were used to determine the influence of storage treatments and crop duration on disease development in crops grown in field plots with a high level of inoculum. Post-harvest black dot was shown to be higher on tubers subjected to an extended-cure treatment than those which had minimal-curing in a maincrop variety that had been grown for more than 130 days from 50% emergence to harvest (P=0.024). The integration of the results from the field and storage components of this three year trial into practical recommendations for the control of black dot will be discussed.
Keywords: Ka; Colletotrichum coccodes; black dot; PCR; Storage